Interferon‐Free Therapy in Elderly Patients With Advanced Liver Disease. (September 2017) - Lens, Sabela; Fernández, Inmaculada; Rodríguez‐Tajes, Sergio; Hontangas, Vanessa; Vergara, Mercedes; Forné, Montserrat; Calleja, Jose Luis; Diago, Moisés; Llaneras, Jordi; Llerena, Susana; Torras, Xavier; Sacristán, Begoña; et al.
Abstract : Objectives: Interferon‐free therapies have an improved safety and efficacy profile. However, data in elderly patients, who have frequently advanced liver disease, associated comorbidities, and use concomitant medications are scarce. The im of this study was to assess the effectiveness and tolerability of all‐oral regimens in elderly patients in real‐life clinical practice. Methods: Retrospective analysis of hepatitis C virus (HCV) patients aged ≥65 years receiving interferon‐free regimens within the Spanish National Registry (Hepa‐C). Results: Data of 1, 252 patients were recorded. Of these, 955 (76%) were aged 65–74 years, 211 (17%) were aged 75–79 years, and 86 (7%) were aged ≥80 years at the start of antiviral therapy. HCV genotype‐1b was predominant (88%) and 48% were previous non‐responders. A significant proportion of patients had cirrhosis (922; 74%), of whom 11% presented decompensated liver disease. The most used regimens were SOF/LDV (33%), 3D (28%), and SOF/SMV (26%). Ribavirin was added in 49% of patients. Overall, the sustained virological response (SVR12) rate was 94% without differences among the three age categories. Albumin ≤3.5 g/dl was the only independent negative predictor of response (0.25 (0.15–0.41); P <0.01). Regarding tolerability, the rate of severe adverse events increased with age category (8.8, 13, and 14%; P =0.04). In addition, the main predictors of mortality (2.3%) were age ≥75 years (2.59 (1.16–5.83); P  =0.02) and albumin ≤3.5 (17 (6.3–47); P  <0.01). Conclusions: SVR rates with interferon‐free regimens in elderly patients are high and comparable to the general population. Baseline low albumin levels (≤3.5 g/dl) was the only predictor of treatment failure. Importantly, the rate of severe adverse events and death increased with age. Elderly patients (≥75 years) or those with advanced liver disease (albumin ≤3.5) presented higher mortality. Thus a careful selection of patients for antiviral treatment is recommended.